HLA-DRB1 and –DQB1 Alleles, Haplotypes and Genotypes in Emirati Patients with Type 1 Diabetes Underscores the Benefits of Evaluating Understudied Populations - Al Yafei, Zain; Mack, Steven J.; Alvares, Marion; Ali, Bassam R.; Afandi, Bachar; Beshyah, Salem A.; Sharma, Charu; Osman, Wael; Mirghani, Rajaa; Nasr, Amre; Al Remithi, Sareea; Al Jubeh, Jamal; et al. (Frontiers in Genetics, 2022)
Background: HLA class II (DR and DQ) alleles and antigens constitute strong genetic predisposition to type 1 diabetes (T1D). This study evaluated the association of DRB1 and DQB1 alleles, genotypes, and haplotypes with T1D in United Arab Emirates. Materials and Methods: Study subjects comprised 149 patients with T1D, and 147 normoglycemic control subjects. Cases and controls were Emiratis and were subjected to HLA-DRB1 and -DQB1 genotyping using sequence-based typing. Statistical analysis was performed using Bridging Immunogenomic Data-Analysis Workflow Gaps R package. Results: In total, 15 DRB1 and 9 DQB1 alleles were identified in the study subjects, of which the association of DRB1*03:01, DRB1*04:02, DRB1*11:01, DRB1*16:02, and DQB1*02:01, DQB1*03:02, DQB1*03:01, and DQB1*06:01 with altered risk of T1D persisted after correcting for multiple comparisons. Two-locus haplotype analysis identified DRB1*03:01~DQB1*02:01 (0.44 vs. 0.18, OR (95% CI) = 3.44 (2.33-5.1), Pc = 3.48 ×10-10; DRB1*04:02~DQB1*03:02 (0.077 vs. 0.014, OR = 6.06 (2.03-24.37), Pc = 2.3 ×10-3) and DRB1*04:05~DQB1*03:02 (0.060 vs. 0.010, OR = 6.24 (1.79-33.34), Pc = 0.011) to be positively associated, and DRB1*16:02~DQB1*05:02 (0.024 vs. 0.075, OR = 0.3 (0.11-0.74), Pc = 0.041) to be negatively associated with T1D, after applying Bonferroni correction. Furthermore, the highest T1D risk was observed for DR3/DR4 (0.104 vs. 0.006, OR = 25.03 (8.23-97.2), Pc = 2.6 ×10-10), followed by DR3/DR3 (0.094 vs. 0.010, OR = 8.72 (3.17-25.32), Pc = 3.18 ×10-8) diplotypes. Conclusion: While DRB1 and DQB1 alleles and haplotypes associated with T1D in Emiratis showed similarities to Caucasian and non-Caucasian populations, several alleles and haplotypes associated with T1D in European, African, and Asian populations, were not observed. This underscores the contribution of ethnic diversity and possible diverse associations between DRB1 and DQB1 and T1D across different populations.